2019
DOI: 10.1016/j.chb.2019.07.006
|View full text |Cite|
|
Sign up to set email alerts
|

Human agency beliefs affect older adults' interaction behaviours and task performance when learning with computerised partners

Abstract: Computer-mediated systems can support aging in-place, although little is known about how older adults interact with these systems and how they learn from them. Using a Wizard-of-Oz paradigm, this study compared how older adults interacted and learned with a system that they believed was a human, and with a system they believed was a computer. While both systems were identical, the human system used natural speech and the computer system used synthetic speech. In a within-subjects design, twenty-four older adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Younger adults did have improved delayed recall United Kingdom PhD thesis non-randomized experimental study 24 N N perceived human versus computer partner adapted version of Map Task older adults modified their interaction when learning with a human or a computer. Older adults recalled fewer details of routes learned with the computer partner and found the learning experience more difficult Crompton & MacPherson [ 85 ] United Kingdom research article non-randomized experimental study 24 N N perceived human versus computer partner referential task/Barrier Task participants in the computer condition were slower, took fewer turns, and recalled less Crompton et al . [ 86 ] United Kingdom research article non-randomized experimental study 48 Y N familiar, unfamiliar referential task/Barrier Task older adults’ performance became indistinguishable from younger adults over time, no effect of familiarity Derksen et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Younger adults did have improved delayed recall United Kingdom PhD thesis non-randomized experimental study 24 N N perceived human versus computer partner adapted version of Map Task older adults modified their interaction when learning with a human or a computer. Older adults recalled fewer details of routes learned with the computer partner and found the learning experience more difficult Crompton & MacPherson [ 85 ] United Kingdom research article non-randomized experimental study 24 N N perceived human versus computer partner referential task/Barrier Task participants in the computer condition were slower, took fewer turns, and recalled less Crompton et al . [ 86 ] United Kingdom research article non-randomized experimental study 48 Y N familiar, unfamiliar referential task/Barrier Task older adults’ performance became indistinguishable from younger adults over time, no effect of familiarity Derksen et al .…”
Section: Resultsmentioning
confidence: 99%
“…This is likely due to the different versions available, including those produced by Clark & Wilkes-Gibbs [ 100 ] and Krauss & Weinheimer [ 101 ]. Some studies used 10 images per trial [ 88 , 89 ] while others used 12 images [ 7 , 85 , 86 , 92 , 98 ]. Also, the number of trials per session differed, with 4 trials [ 88 , 98 ], 6 trials [ 7 , 87 , 89 ], 9 trials [ 85 , 86 ] or more [ 92 ] per condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the human factor, the AlgoRythmics approach relates to some results in the field of neuroscience of social cognition and pedagogical agents. A number of studies have linked specific brain circuits to certain aspects of social perception and interaction (Crompton & MacPherson, 2019). For instance, it was observed that certain regions of our brain shows higher sensitivity to images of human faces and bodies compared to images of objects (Downing et al, 2001; Kanwisher et al, 1997).…”
Section: Theoretical Backgroundmentioning
confidence: 99%